PERSPECTIVE HYDROSTATIC-MECHANICAL TRANSMISSIONS FOR WHEELED TRACTORS OF AGRICULTURAL SETTING - Samorodov, V.; Bondarenko, A. (Avtomobilʹnyj Transport (Harʹkov), 2013)
The kinematics charts of perspective hydrostatic-mechanical transmission are presented, their basic structural parameters, the size of hydraulic machines of hydrostatic transmission are identified, the kinematic and power parameters of transmissions are determined.